SWOT ANALYSIS AS TOTAL QUALITY MANAGEMENT TOOL: A SYSTEMATIC ANALYSIS BETWEEN PAKISTAN AND MALAYSIA PUBLIC UNIVERSITIES - Muhammad Naveed Jabbar (PhD); Farah Qadir Malik; Haq Nawaz (PhD) (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The present study narrow downs the quality management measures, standards and guidelines at global level. Moreover, focusing over review of literature related to education sector with respect to total quality management. The main objective of this research was to determine the SWOT analysis as TQM tool among Pakistan and Malaysia universities. The teaching faculty members of the public universities were the population whereas, 413 (Pakistan 219, Malaysian 194) respondents were selected as sample through simple random sampling technique. A survey method was administered to collect the data from the participants by using self-administered questionnaire. SPSS-25 was directed to analyze the data. The findings show that the Pakistan and Malaysia public universities focus on the strategies and techniques that enhance the quality of services. Furthermore, it concluded that quality of Malaysian higher education institutions is better than Pakistani universities. The study is helpful to adopt the innovative techniques for the development of quality of services.